Population Density and Distribution Pattern of Golden Apple Snail (Pomacea canaliculata L.) in the Rice Field Ecosystem - Sinta Sinta; Sutrisnawati Sutrisnawati; Manap Trianto; Masrianih Masrianih; Rafiqah Rafiqah; Fatmah Dhafir (Biology, Medicine, & Natural Product Chemistry, 2026)
The golden apple snail (Pomacea canaliculata) is a freshwater mollusc species commonly found in rice field ecosystems and is recognized as one of the major pests of rice crops. This species possesses a high adaptive capacity and a rapid reproductive rate, allowing its population to increase rapidly and cause significant damage to rice plants. Nevertheless, the golden apple snail also has ecological roles and potential benefits, including serving as an alternative feed source for livestock and fish, as well as contributing to the decomposition of organic matter in aquatic environments. This study aimed to analyze the population density and distribution pattern of the golden apple snail in the rice fields of Dolago Padang Village, South Parigi District. The research employed a quantitative descriptive approach using a field survey method. Data were collected using a quadrat sampling technique with plot sizes of 2 × 2 m established at three different observation stations. The number of golden apple snail individuals within each plot was counted directly and subsequently analyzed to determine population density and distribution patterns using the Morisita Index. In addition, environmental parameters, including water temperature and pH, were measured. The results showed that a total of 90 golden apple snail individuals were recorded during the study. Population density ranged from 1 to 2 individuals/m², which was categorized as moderate. The distribution pattern of the golden apple snail at all observation stations was classified as uniform, as indicated by Morisita Index values below 1 (Id < 1). Environmental conditions, with temperatures ranging from 27–30°C and pH values between 6.5 and 7.2, were within the optimal range supporting the presence and development of the golden apple snail.